Divulgación de la información falsa, caso: Paro nacional medidas económicas, Ecuador 2019 - Peñafiel España, Lilibeth Leonela (2020)
The present case analysis was based on the disclosure of false information, case: National unemployment measures, Ecuador 2019, with the aim of carrying out an analysis of the consequences derived from this problem and thus being able to highlight the social need to verify the information prior to release. The techniques that were used were; observation through content disseminated on social networks and traditional media, bibliographic research and interviews conducted with Lcda. María Flores and the journalist Gisela Garcés, who allowed obtaining first-hand information on the problem. Throughout this research project, the different types of erroneous content that existed and the effect they caused are exposed, in depth the attack on journalists, public entities, politicians and the media by citizens is highlighted, among other events that happened during the demonstrations. Ecuador is questioned for the lack of a law that penalizes the disclosure of false information. In addition, journalists and companies that worked during the protests in the verification of information are highlighted and it was confirmed that social networks are the main sources of disinformation, generating a loss of trust towards digital media.